2019
DOI: 10.3389/fnmol.2019.00227
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Restoration of Serotonin-Immunoreactive Paraneuronal Cells During Caudal Fin Regeneration in Zebrafish

Abstract: Aquatic vertebrates possess diverse types of sensory cells in their skin to detect stimuli in the water. In the adult zebrafish, a common model organism, the presence of such cells in fins has only rarely been studied. Here, we identified scattered serotonin (5-HT)-positive cells in the epidermis of the caudal fin. These cells were distinct from keratinocytes as revealed by their low immunoreactivity for cytokeratin and desmosome markers. Instead, they were detected by Calretinin (Calbindin-2) and Synaptic ves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…This robust nature is not unexpected for immune and brain network system 26,27 , as the DE genes of the lg KO line are mainly neurons and immunity related genes. Besides, lineage-specific new genes initially usually located at the edge of the gene network 28 29 ; in pharyngeal cartilages, the wellknown tissues related to feeding and ecological niche exploration, are key to cichlid fish adaptive radiation [30][31][32] ; in scattered epidermal serotonin-positive cells which are neuroepithelia cells related to environmental stimuli, such as water flow, pheromone and hormone 33,34 ; in the olfactory epithelium which is well-known for detection of odorants, such as amino acid, hormone and pheromone 35 . Considering that some of these tissues are derived from a key vertebrate innovation, the neural crest cells 36 , lg can be also causally linked to neural crest cell development and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This robust nature is not unexpected for immune and brain network system 26,27 , as the DE genes of the lg KO line are mainly neurons and immunity related genes. Besides, lineage-specific new genes initially usually located at the edge of the gene network 28 29 ; in pharyngeal cartilages, the wellknown tissues related to feeding and ecological niche exploration, are key to cichlid fish adaptive radiation [30][31][32] ; in scattered epidermal serotonin-positive cells which are neuroepithelia cells related to environmental stimuli, such as water flow, pheromone and hormone 33,34 ; in the olfactory epithelium which is well-known for detection of odorants, such as amino acid, hormone and pheromone 35 . Considering that some of these tissues are derived from a key vertebrate innovation, the neural crest cells 36 , lg can be also causally linked to neural crest cell development and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…While an earlier study showed 5HT immunoreactive cells on gill papillar epithelium (Suntres, ), this localization was not confirmed in later experiments. While SCCs were not 5‐HT‐immunoreactive in the sea lamprey, 5HT is localized in the gustatory taste cells (Barreiro‐Iglesias et al, ) and 5HT, calretinin and SV2 immunoreactive cells are present in the epidermis of zebrafish fins (Konig et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the tangential shear stress may have a particular significance in certain hydrodynamic problems, even when the flow is dominated by the fluid inertial forces. For instance, resolving the viscous shear stress maps on the surface of fin models might be informative in problems related to flow sensing in the skin of fish [ 111 ]. In other words, despite the lower order of magnitude of the measured viscous tangential stress, these components may be of special interest for certain biological applications, which is why we retained them in our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In the present work, the focus is on providing an estimate of both hydrodynamic stress contributions (shear stress and pressure) from instantaneous captures of the three-dimensional flow field, which requires a compromise between the size of the measurement volume and the vector field spatial resolution. In a recent study, we showed that it is possible to resolve the velocity field inside the shear layer forming over a flat plate pitching in a similar flow regime using the same volumetric PTV experimental setup [ 111 ]. In that case, the boundary layer thickness, defined as the distance at which the velocity reaches 99% of the free-stream value, varied dynamically between ∼2 and 6 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation